(untitled) (Dissertare, 2017)
This article presents preliminary results of an investigation, whose objective is to design a theatrical program, as an educational strategy to strengthen values ​​of cultural identity in girls and boys of the community "El Limoncito", of Araure Municipality, Portuguesa State (Venezuela). The research is predominantly quantitative, with some aspects of the qualitative approach and is part of the projective category, with field design, under the feasible project modality, which consists of three phases: diagnosis, feasibility and design. In this research progress, the first two are covered. The data collection includes the use of two techniques: survey and focus group. The first is based on the application of two questionnaires addressed to an equal number of samples, one for families and another for educators. The focus group was formed with key community actors, including educators, community leaders and members of cultural groups. The data derived from the questionnaires will be analyzed using descriptive statistics, while the information obtained from the focus group was processed through content analysis. The preliminary results of the research show the lack of actions to promote cultural identity in the community studied. In the same way, elements that support the feasibility of applying the strategy based on theater, to strengthen the cultural identity of children in the context analyzed, are revealed. Based on these findings, it is concluded that it is necessary to develop actions to reinforce the cultural identity in the aforementioned community, to which the proposed strategy can contribute.